2008
DOI: 10.1158/0008-5472.can-07-2751
|View full text |Cite
|
Sign up to set email alerts
|

Tristetraprolin Down-regulates Interleukin-8 and Vascular Endothelial Growth Factor in Malignant Glioma Cells

Abstract: Malignant gliomas are highly aggressive tumors of the central nervous system that rely on production of growth factors for tumor progression. Vascular endothelial growth factor (VEGF), interleukin-8 (IL-8), and tumor necrosis factor-A, for example, are up-regulated in these tumors to promote angiogenesis and proliferation. RNA stability, mediated through adenine and uridine-rich elements (ARE) in the 3 ¶ untranslated region, is a critical control point for regulating these growth factors. RNA half-life is pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
106
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(114 citation statements)
references
References 43 publications
6
106
0
2
Order By: Relevance
“…In the same cells, we also observed a necrotic cleavage of PARP-1 that further suggests that the ZFP36 induced cell death of ln827 GBM cells could depend on a necroptotic cell death program. Altogether, these data suggest that by restoring the expression of ZFP36, ln827 GBM cells die owing to the activation of two Moreover, there is evidence suggesting that ZFP36 is inactivated in gliomas, 17 and we collected further evidence (Fig. 1A) that in ln827 GBM cell lines, ZFP36 is expressed at very low levels.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In the same cells, we also observed a necrotic cleavage of PARP-1 that further suggests that the ZFP36 induced cell death of ln827 GBM cells could depend on a necroptotic cell death program. Altogether, these data suggest that by restoring the expression of ZFP36, ln827 GBM cells die owing to the activation of two Moreover, there is evidence suggesting that ZFP36 is inactivated in gliomas, 17 and we collected further evidence (Fig. 1A) that in ln827 GBM cell lines, ZFP36 is expressed at very low levels.…”
Section: Discussionmentioning
confidence: 59%
“…15 As regards cancer biology, it has been shown that ZFP36 may alter the tumorigenic phenotype and patient prognosis, 16 probably targeting several oncogenes. ZFP36 is downregulated in many cancers, and, in particular, it has been shown that ZFP36 is hyperphosphorylated and therefore inactive in gliomas, 17 this leading to stabilization of VEGF and IL-8 mRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian cancer cells produce TNF-a and CXCL8 upon p38a MAPK activation, and these cytokines may act in an autocrine manner to promote peritoneal colonization and tumor vascularization (21). The U-87MG glioma, A-2780 and SK-OV-3 ovarian cancers, and PC3 prostate cancer all secrete VEGF, basic fibroblast growth factor (bFGF), EGF, and IL-6; and importantly, secretion of these cytokines can be significantly reduced by p38 MAPK inhibition (6,22). Furthermore, pretreatment of tumor cells with LY2228820 or p38a MAPK short hairpin RNA (shRNA) reduces cord formation in a tumor/adipocyte-derived stem/endothelial colony-forming cell coculture system, supporting a p38 MAPK-mediated effect of the tumor on the TME (6).…”
mentioning
confidence: 99%
“…Moreover, a lack of TTP is associated with a variety of cancer-related processes (Brennan et al, 2009). In this respect, regulation of TTP expression has been shown to play a role in several cancers such as colon, breast, skin, lung, and brain (Lee et al, 2013;Suswam et al, 2008). However, its role in glioma has not been fully investigated.…”
Section: Discussionmentioning
confidence: 99%